The accuracy of judgments of learning (JOLs) and the mnemonic keyword method in elderly adults - Alfredo Campos; Leticia Ameijide (International Journal of Psychological Research, 2011)
The aim was to assess the efficacy of the keyword mnemonic method and its impact on the accuracy of Judgments of Learning (JOLs) in elderly adults. The sample consisted of a hundred participants aged 65 to 86, who were subdivided into two age groups: 65-75 years and 76-86 years. Each group had to learn, using either their own habitual method of learning or the mnemonic keyword method, the Spanish meaning of a list of keywords in Latin that had high image vividness scores. The 76-86 year age group, who tended to use their own habitual method as opposed to the mnemonic keyword method, obtained higher accuracy scores than the 65-75 year age group.